Characterization of a member of the CEACAM protein family as a novel marker of proton pump-rich ionocytes on the zebrafish epidermis. - Julien Kowalewski; Théo Paris; Catherine Gonzalez; Etienne Lelièvre; Lina Castaño Valencia; Morgan Boutrois; Camille Augier; Georges Lutfalla; Laure Yatime (PLoS ONE)
In humans, several members of the CEACAM receptor family have been shown to interact with intestinal pathogens in an inflammatory context. While CEACAMs have long been thought to be only present in mammals, recent studies have identified ceacam genes in other vertebrates, including teleosts. The function of these related genes remains however largely unknown. To gain insight into the function of CEACAM proteins in fish, we undertook the study of a putative member of the family, CEACAMz1, identified in Danio rerio. Sequence analysis of the ceacamz1 gene product predicted a GPI-anchored extracellular protein containing eleven immunoglobulin domains but revealed no evident orthology with human CEACAMs. Using a combination of RT-PCR analyses and in situ hybridization experiments, as well as a fluorescent reporter line, we showed that CEACAMz1 is first expressed in discrete cells on the ventral skin of zebrafish larvae and later on in the developing gills. This distribution remains constant until juvenile stage is reached, at which point CEACAMz1 is almost exclusively expressed in gills. We further observed that at late larval stages, CEACAMz1-expressing cells mostly localize on the afferent side of the branchial filaments and possibly in the inter-lamellar space. Using immunolabelling and 3D-reconstructions, we showed that CEACAMz1 is expressed in cells from the uppermost layer of skin epidermis. These cells are embedded within the keratinocytes pavement and we unambiguously identified them as proton-pump rich ionocytes (HR cells). As the expression of ceacamz1 is turned on concomitantly to that of other known markers of HR cells, we propose that ceacamz1 may serve as a novel marker of mature HR cells from the zebrafish epidermis.